1998
DOI: 10.1046/j.1472-765x.1998.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antimicrobial effect of nisin whey permeate and lactic acid on microbes isolated from fish

Abstract: A. NYKÄ NE N, S . V ES A NE N A N D H . K A LL IO . 1998. The antimicrobial activity of a combination of lactic acid and whey permeate fermented by a nisin-producing Lactococcus lactis strain was tested by the agar diffusion method using bacteria isolated from fish as test organisms. Lactic acid inhibited all bacterial strains studied, but nisin whey permeate inhibited Gram-positive bacteria only. The combination was more effective than lactic acid alone against Pseudomonas fluorescens and Staphylococcus homin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Nisin and lactic acid act synergically on P. fluorescens and Staph. hominis isolated from fish (Nykänen et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nisin and lactic acid act synergically on P. fluorescens and Staph. hominis isolated from fish (Nykänen et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [54][55][56] have demonstrated that nisin is an e#ective bactericidal peptide against Gram negative bacteria if the cells are previously or simultaneously treated with other compounds like EDTA, lactic acid and other organic acids. This may explain why, in our experiments, the serum bactericidal activity against E. coli seemed not to be a#ected by nisin treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, lowering of the salt content of food or omission of preservatives will encourage growth of microorganisms (Nykanen et al, 1998). To ensure microbiological safety of foods, alternative means of preservation must be developed.…”
Section: Introductionmentioning
confidence: 99%